2015
DOI: 10.1007/s13258-015-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating omics analysis of salt stress-responsive genes in rice

Abstract: The detrimental effect of high salinity on crop production is a serious problem. However, the number of genes with known functions relating to salinity tolerance is very limited in rice. To effectively address this limitation, selection of useful candidate genes and identification of major regulatory factors through global approaches are necessary. To this end, we used three data series of affymetrix array data produced with salt-treated samples from NCBI Gene Expression Omnibus (http://www.ncbi.nlm. nih.gov/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…5c, Additional file 8: Table S7). Similar results were also reported in previous studies, which suggested that plant salt tolerance is a complex regulating network involving in signal transduction, and substance and energy metabolism [44, 45].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…5c, Additional file 8: Table S7). Similar results were also reported in previous studies, which suggested that plant salt tolerance is a complex regulating network involving in signal transduction, and substance and energy metabolism [44, 45].…”
Section: Resultssupporting
confidence: 91%
“…In Arabidopsis, overexpression of OsPP108 , a group A type PP2C from rice, increased the plant’s insensitive to ABA and tolerance to high salt and mannitol stresses during seed germination, root growth, and overall seedling growth [40]. Plant growth is mainly the results of cell division and elongation, while salt stress inhibits cell division and cell wall metabolism [44, 46]. A decrease in cell wall extensibility has been suggested to be responsible for leaf growth reduction under salt stress [47, 48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of Os03g0820400 (TFmatrixID_0216) was induced by cold more than four-fold in rice cold tolerant cultivar Oro (da Maia) [ 51 ]; Os10g0377300 (TFmatrixID_0298) was typed as candidate genes related to low-temperature tolerance [ 52 ]; whereas Os12g0123700 (TFmatrixID_0381) and Os02g0170300 (TFmatrixID_0529) were found to be cold-responsive in rice and Oryza ofcinalis [ 53 ]. Among other abiotic stresses, binding sites recognised by TFs involved in plant responses to drought [ 54 , 55 , 56 , 57 ], salt [ 58 , 59 , 60 ], arsenic [ 61 ], cadmium [ 62 ], nitrogen [ 63 , 64 ] or iron [ 65 ] deficiency were identified ( Table 1 ; Table S3 ). Binding sites of TFs that play a role in plant response to pathogen attack, such as viruses [ 66 ], bacteria [ 67 ] or fungi [ 68 ], were also present.…”
Section: Resultsmentioning
confidence: 99%
“…We extracted total RNA from whole seedlings and synthesized cDNA using methods introduced previously 88 , 89 . The quality of cDNA samples was validated and evaluated with two drought-responsive marker genes ( Oryza sativa dehydration-responsive element binding transcription factor 2b , or OsDREB2b , and OsbZIP23 ), the daytime-expressed Oryza sativa Late Elongated Hypocotyl ( OsLHY ), and the nighttime-expressed Heading Date 1 ( HD1 ) (Figure S6 ) 90 93 .…”
Section: Methodsmentioning
confidence: 99%